Elena, princesa of the periphery : Disney's flexible Latina girl - Leon-Boys, Diana (New Brunswick, New Jersey : Rutgers University Press, 2023)
"In the summer of 2016, Disney introduced its first Latina princess, Elena of Avalor. Princesa of the Periphery explores this Disney property using multiple case studies to understand its approach to girlhood and Latinidad. Following the circuit of culture model, author Diana Leon-Boys teases out moments of complex negotiations by Disney, producers, and audiences as they navigate Elena's circulation. Case studies highlight how a flexible Latinidad is deployed through corporate materials, social media pages, theme park experiences, and the television series to create a princess who is both marginal to Disney's normative vision of princesshood and central to Disney's claims of diversification. This multi-layered analysis of Disney's mediated Latina girlhood interrogates the complex relationship between the U.S.'s largest ethnic minority and a global conglomerate that stands in for the U.S. on the global stage"--
Introduction: Latina girls' media studies -- From Black-and-White mouse to "Latina" girl -- The flexible production of a "Latina" princess -- Animated Latina girlhood and the continuum of flexibility -- On-site performance of Latinidad from East Coast to West Coast -- Conclusion: A princess for all is a princess without a home.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Elena of Avalor (Television program); Disney Channel (Firm); Disney Channel (Firm); Elena of Avalor (Television program); Hispanic American women on television; Disney characters; Girls on television; Branding (Marketing); Personnages de Disney; Stratégie de marque; branding; SOCIAL SCIENCE / General; Branding (Marketing); Disney characters; Girls on television; Hispanic American women on television; Electronic books